Effect of kitchen/fermented rice waste on nutrient utilization by native pigs - KUMAR, S; SINHA, A P; SINGH, R N; SINGH, S K; THAKUR, S (The Indian Journal of Animal Sciences, 2011)
The present study was conducted with 45 growing native pigs divided into 5 equal groups. The pigs in control group (T1) were fed on grower ration (CP 18.04% and DE 2.94 Mcallkg) 75.00% of which was replaced on DM basis with kitchen waste (T2)’ kitchen and fermented rice waste combined in equal proportion (T3)’ kitchen waste completely (T4) or kitchen waste and fermented rice waste combined equal proportion completely (T5)’ Digestibility of DM, OM, CP, EE, NFE and balances of N, Ca and P increased with the increase in the proportion of kitchen waste in swine rations leading to higher nutrient utilization. Â